محددات الناتج المحلي الإجمالي خارج قطاع المحروقات في الجزائر خلال الفترة 1998-2020 - غفوري حبيبة منة الرحمان; رملي حمزة (جامعة الوادي University of Eloued, 2023)
This study aims to measure the impact of some economic variables on GDP outside the hydrocarbon sector in Algeria during the period 1998-2020, and to achieve this goal, the ARDL method was used, and the study concluded that there is a direct relationship between GDP outside the hydrocarbon sector. Both public spending, employment rate and exports outside the hydrocarbon sector, and the most important economic variables affecting the determinants of GDP outside the hydrocarbon sector are public spending, employment rate and exports outside the hydrocarbon sector
Determinants of GDP outside the hydrocarbon sector in Algeria during the period 1998-2020
Keywords: الناتج المحلي الإجمالي; التشغيل; الانفاق العام; الصادرات; سعر الصرف; public expenditure; exports; exchange rate; ARDL methodology